(untitled) (LSP International Journal, 2019)
Recent studies have suggested that literature components benefit students in language acquisition and reading in general, yet reading for enjoyment is arguable since most of the students admit reading is done for examination purposes. Regardless of the reading purpose, adoption of efferent, aesthetic and critical stances is vital and believed to influence the reading process. The main purpose of this study is to investigate the perceived and actual reading stances among learners when they read a novel. A total of 484 students from twelve non-residential secondary schools situated in Kuantan participated in this study. Employing a mixed method design, both quantitative and qualitative research approaches were utilised. The instruments used to collect the data were a set of questionnaire and student’s written responses. Although the findings from the questionnaire and written responses suggested that the learners employed all the three stances namely efferent, aesthetic and critical stances, there was the tendency for the students to adopt more of the efferent stance than the aesthetic and critical stances. Overall, the adoption of the efferent stance indicates that the students tend to closely and narrowly process the novel in terms of the story line narrated by the writer rather than adopting aesthetic and critical stances through interacting with the plot and characters and relating these elements with their experience and viewpoints.